Selective C(8)–H Activation of Imidazopyridines Mediated by Cooperative Nickel–Aluminum Catalysis - Liu, Cheng-Yuan; Chen, Ying-Ho; Chen, Chih-Hao; Yu, Ming-Shiuan; Tsai, Fu-Yu; Ong, Tiow-Gan (Synthesis, 2016)
A catalytic paradigm is described featuring a synergistic interaction between nickel, aluminum and different ligands to impart a rather remote C–H alkenylation of imidazo[1,5-a]pyridines at the C-8 position without the necessity of installing a directing group. The scope of the direct C–H activation reactions of various 5-aryl- and 3-arylimidazopyridines is established using different sterically hindered alkynes.
Keywords: C–H activation; nickel; aluminum; imidazopyridines; cooperative catalysis